KKN REGULER DI PADUKUHAN KLIPUH DAN BONOREJO KALURAHAN GULUREJO KAPANEWON LEDAH KULON PROGO - Rodli, Ahmad; Kusumawati, Intan; Rohmah, Iffah Nurtaria; Trisnawati, Ika Rahayu (Gemi: Jurnal Penelitian dan Pengabdian, 2024)
KKN was carried out on February 2, 2022. The implementation of the KKN program started from observations carried out after the deployment. Observations were made as a reference for the preparation of the KKN work program that had been carried out in Klipuh and Bonorejo Padukuhan, Gulurejo Village, Kapanewon Lendah, Kulon Progo Regency, Daerah Istimewa Yogyakarta from February 2, 2022 to March 17, 2022. With this observation, students can plan work programs that have been carried out during the implementation of KKN in Padukuhan Klipuh and Bonorejo. The results of the group and individual work programs were carried out well. The response from the community is also very good. The community helps a lot in the work programs that we carry out. Funding for the implementation of the KKN program originating from the campus is given to each student and student fees. The implementation of the overall program is in accordance with the plan. Population factors in the implementation of the KKN work program include the cohesiveness of group members, the families of Mr and Mrs who have provided a place for us to live.